A STUDY OF GENDER-BASED DIFFERENCES IN MULTIPLE INTELLIGENCES - Karnika Saxena1, Dr. Sushma Kela2 and Dr. Varsha Sharma3 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This study explores gender-based differences in multiple intelligences among secondary school students (11th standard) from Bhopal City areas. The sample consists of male and female students. To evaluate their multiple intelligences, a standardized Multiple Intelligence Scale is employed. The research aims to determine the relationship between gender and intelligence profiles while considering the influence of geographic location. The findings provide insights into variations in intelligence types among genders and how these differences correlate with academic achievement. This study has implications for educators in tailoring instruction to diverse learning needs and promoting inclusive educational practices.